Roraima: movimento indígena, demarcação de terra e conflito social - Alonso, Victor Federico (2013)
This study aims at improving knowledge of social relations in the Brazilian state of Roraima. On the one hand, an attempt was made to show how a sovereignty has been constructed throughout history on the molds of coronelism and clientelism; and then how these types of patronage have continued until the present and fostered a divided society, one that is filled with land-ownership conflicts, land occupation, violence and prejudice. On the other hand, an analysis was made of the rise and organization of a cohesive indigenous movement called Conselho Indígena de Roraima (Indigenous Council of Roraima), as well as of how the movement came to be a political alternative to the once exclusive power of the oligarchy. A study was carried out about the achievements of the movement, especially on land demarcation, and also about the problems it has faced, especially in getting society in the capital of the state to support it. This analysis used books from anthropologist, sociologists, political scientists, historians, as well as, magazines and newspapers articles, theses, academic journals, travel and analyzed the speeches from Congressmen and the vote of the Supreme Court